UNIT 17.2 Electron Microscopy and Image Processing: Essential Tools for Structural Analysis of Macromolecules. (2nd November 2015) - Belnap, David M.
Abstract : Macromolecular electron microscopy typically depicts the structures of macromolecular complexes ranging from ∼200 kDa to hundreds of MDa. The amount of specimen required, a few micrograms, is typically 100 to 1000 times less than needed for X‐ray crystallography or nuclear magnetic resonance spectroscopy. Micrographs of frozen‐hydrated (cryogenic) specimens portray native structures, but the original images are noisy. Computational averaging reduces noise, and three‐dimensional reconstructions are calculated by combining different views of free‐standing particles ("single‐particle analysis"). Electron crystallography is used to characterize two‐dimensional arrays of membrane proteins and very small three‐dimensional crystals. Under favorable circumstances, near‐atomic resolutions are achieved. For structures at somewhat lower resolution, pseudo‐atomic models are obtained by fitting high‐resolution components into the density. Time‐resolved experiments describe dynamic processes. Electron tomography allows reconstruction of pleiomorphic complexes and subcellular structures and modeling of macromolecules in their cellular context. Significant information is also obtained from metal‐coated and dehydrated specimens. © 2015 by John Wiley & Sons, Inc.